2017
DOI: 10.1007/s00167-017-4465-2
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical variations of flexor hallucis longus tendon increase safety in hindfoot endoscopy

Abstract: During hindfoot endoscopy, the presence of an anatomical variant related to the FHL tendon has proven safer anatomically than in its absence, due to the increased distance between the FHL tendon and the tibial neurovascular bundle in the working area. However, the minimal difference observed in safety distances still poses a major risk of injury during hindfoot endoscopic procedures in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…However, a pitfall to posterolateral approach is that the SN is at risk of injury (Ellapparadja, 2013). Therefore, a deep understanding of the clinical anatomy of the SN, as portrayed by our map, is important to avoid iatrogenic injury (Vega, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a pitfall to posterolateral approach is that the SN is at risk of injury (Ellapparadja, 2013). Therefore, a deep understanding of the clinical anatomy of the SN, as portrayed by our map, is important to avoid iatrogenic injury (Vega, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the presence of anatomical variants around the FHL tendon (ie, low-lying muscular belly or flexor digitorum accessorius longus) increases the distance between the FHL and the neurovascular bundle, therefore increasing the safety of the hindfoot endoscopy, although not making it risk free. 36 Although no complications were observed during tendon harvesting, care should be taken when performing the procedure. An anatomical study is required to draw recommendations on the most adequate place for harvesting, and at the moment, it is at the surgeon's discretion.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between the neurovascular bundle and the FHL tendon has been studied. 17,21,36 Proximally to zone 2, the medial calcaneal branch of the tibial nerve has been located at 1.3 ± 0.5 mm from the tendon and the branch for the abductor digiti quinti muscle at 1.4 ± 0.5 mm. 17 In addition, the tibial nerve is tight and displaced proximally when the ankle is positioned in dorsiflexion, reducing the distance between the nerve and the FHL tendon.…”
Section: Discussionmentioning
confidence: 99%
“…retrotalar tunnel. [15][16][17][18][19] It not only addresses a local tendon problem but also restores the normal functional anatomy of the foot by drastically improving local and remote biomechanics. 5 The arthroscopically assisted section of the retrotalar pulley and the subsequent re-establishment of the tendon glide restore the subtalar mobility and allow the kinetic chain of the lower extremity to regain its natural dynamic balance, as we observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“… 11 , 12 , 13 , 14 Furthermore, this technique provides a good alternative to the already existing open surgical approaches for FHL release and represents the first technique described to address the issue of FHL conflict during its passage through the retrotalar tunnel. 15 , 16 , 17 , 18 , 19 It not only addresses a local tendon problem but also restores the normal functional anatomy of the foot by drastically improving local and remote biomechanics. 5…”
Section: Discussionmentioning
confidence: 99%